Environmental Sanitation and Students’ Welfare in the University of Uyo, Akwa Ibom State - Jane Essien; Unwana-Abasi Udoh; Atairet Atairet (INTERNATIONAL JOURNAL OF PUBLIC RELATIONS AND SOCIAL SCIENCES, 2026)
The study determined the extent to which environmental sanitation variables (restroom facilities and water supply) impact students’ welfare at the University of Uyo, Uyo, Akwa Ibom State. To achieve this, two specific objectives were stated, two research questions were raised and two hypotheses were formulated to guide the study. Planned behaviour theory (1980) by Ajzen and Fishbein was adopted for the study. Descriptive research design was used for the study. The population of the study comprised 45,639 students from the University of Uyo, Uyo, Akwa Ibom State. A multi-stage sampling approach was used for selecting 2,280 students, which represents 5% of the population. An instrument titled Environmental Sanitation Questionnaire (ESQ) and Students’ Welfare Questionnaire (SWQ) was used for data collection from students. The reliability of the instrument was determined using Cronbach's alpha analysis, and the index reliability coefficient of 0.91 was realised and utilised for ESQ and 0.81 for SWQ. Simple linear regression statistics were used to answer the research question and to test the null hypothesis at the .05 significance level. Findings of the study revealed inadequate and insufficient restroom facilities and water supply when measured with the student population at the University of Uyo, and when answering the research questions, low impact of restroom facilities and water was obtained on students’ welfare. Also, the finding revealed that restroom facilities and water supply significantly impacted students’ welfare independently at the University of Uyo. It was concluded that restroom facilities and water supply should simultaneously be in use to boost students’ welfare, leading to a better improvement in students’ health, well-being, comfortable learning environment and hostels. It is recommended that the University of Uyo Management should prioritise investment in building and improving toilet facilities, including regular cleaning across all school blocks and hostels, to improve students' physical comfort and reduce stress-related unclean or unavailable toilets.